Infection by bovine Alphaherpesvirus 1 and 5 and the induction of mucosal immunity (Research, Society and Development, 2022)
The immune system present in the mucosa represents the initial barrier against infection by several pathogens that use these surfaces as a gateway to the host organism, such as the case of bovine Alphaherpesvirus 1 (BoHV-1) and bovine Alphaherpesvirus 5 (BoHV-5). These viruses infect the reproductive and respiratory systems of cattle and are responsible for cases of Infectious Bovine Rhinotracheitis, Infectious Pustular Vulvovaginitis and Infectious Pustular Balanopostitis, as well as Bovine Herpetic Meningoencephalitis, respectively. Infection by BoHVs occurs in cavities lined with mucosal epithelial cells, mainly nasal and genital, being the initial point of replication, followed by local dissemination, eventual viremia and neuronal dissemination, until latency is established. The cooperation of defense mechanisms provides protection through the integrated mucosal system through the activation of effector sites and especially the production of different isotypes of immunoglobulins, such as SIgA, which neutralizes mucosal surfaces, and IgG, which plays a neutralization in the mucosa and systemically. The induction of immunity on mucosal surfaces through the use of vaccines is extremely important for the prevention of virus adsorption to the cell and infection by pathogenic microorganisms and depends, especially, on the immunogen, immunization route and adjuvant substance used in the formulations. This review aimed to address the main aspects related to infection by BoHV-1 and BoHV-5, as well as the types of response related to the mucosal immune system against these viruses, and also studies related to the use of the mucosal pathways for administration of vaccines in different animal species.